2011
DOI: 10.1177/0306396811406781
|View full text |Cite
|
Sign up to set email alerts
|

The shaping of Islam and Islamophobia in Belgium

Abstract: The author discusses the way in which Islam has been cast as a political problem in Belgium and how Muslims have, particularly in Flanders, become framed by politicians and commentators in the media as a threat. The actual socioeconomic difficulties that Muslims (particularly those of Turkish and Moroccan descent) face are being redrawn as problems stemming from their culture and religion. State agencies are trying to shape the political organisation that will represent Belgian Muslims, as the issue of Islam i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 2 publications
0
16
1
1
Order By: Relevance
“…Although we could conceptualize their pathways as (at risk of) downward assimilation (Portes and Zhou 1993), we will use this terminology carefully, since it might label this group even more as a problematic minority, giving rise to racist ideas and actions rather than to scrutinizing the ways in which educational systems and labour market mechanisms are unfair to some groups in society, and to taking action to assure equal opportunities for everyone (Alba, Kasinitz, and Waters 2011). Research has shown extensively how people who are (seen as) Muslims, which in Belgium often comes down to people of Moroccan or Turkish descent, have to cope with very negative attitudes towards them (Zemni 2011). While their socio-economic problems are often related to their perceived ethnic, cultural and/or religious affiliations (Zemni 2011), seldom are reflections made about the fact that some responsibility might also lie with the majority population and that adjusting the context might help significantly (Meuleman and Billiet 2003;Zemni 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we could conceptualize their pathways as (at risk of) downward assimilation (Portes and Zhou 1993), we will use this terminology carefully, since it might label this group even more as a problematic minority, giving rise to racist ideas and actions rather than to scrutinizing the ways in which educational systems and labour market mechanisms are unfair to some groups in society, and to taking action to assure equal opportunities for everyone (Alba, Kasinitz, and Waters 2011). Research has shown extensively how people who are (seen as) Muslims, which in Belgium often comes down to people of Moroccan or Turkish descent, have to cope with very negative attitudes towards them (Zemni 2011). While their socio-economic problems are often related to their perceived ethnic, cultural and/or religious affiliations (Zemni 2011), seldom are reflections made about the fact that some responsibility might also lie with the majority population and that adjusting the context might help significantly (Meuleman and Billiet 2003;Zemni 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Research has shown extensively how people who are (seen as) Muslims, which in Belgium often comes down to people of Moroccan or Turkish descent, have to cope with very negative attitudes towards them (Zemni 2011). While their socio-economic problems are often related to their perceived ethnic, cultural and/or religious affiliations (Zemni 2011), seldom are reflections made about the fact that some responsibility might also lie with the majority population and that adjusting the context might help significantly (Meuleman and Billiet 2003;Zemni 2011). The same mechanisms seem to be at work in schools: teachers and school principals acknowledge that youngsters with a migration background are more often oriented towards non-general educational trajectories and that this is problematic (Clycq et al 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no complexity in Huntington's and Lewis's vision, and it is not difficult to see, embedded within their frameworks, a continuation of the old colonial mentality in which the rational and individualistic culture of 'the West' is treated as 'an exception in the history of mankind' at the same time as 'Islam is treated as a pariah in the history of religions, just as Europe and the West did so well in the past with Judaism'. 44 Some centre-right European political leaders have embraced the clash of civilisations theme, notably the Italian prime minister Silvio Berlusconi and the current Danish interior minister Søren Krarup, who described the invasion of Iraq in 2003 as resulting from the 'opposition between Christianity and Islam, between the West and Islam'. Krarup has also compared the fight against Islam with the fight against Nazism in Germany in the 1930s.…”
Section: Clash Of Civilisationsmentioning
confidence: 99%
“…Similar debates were triggered in the case of the Via Rail terrorist plot in Canada that came to the media's attention at about the same time as the Boston Marathon bombing. Debates and depictions like these have been rampant in the media and have increased ever since the events of September 11, 2001 and the "War on Terror" (see Echchaibi, 2013a;Martin and Phelan, 2002;and Zemni, 2011).…”
Section: Stepping Into the Mediascape: Muslims Telling Their Own Storiesmentioning
confidence: 99%